Behavioral interventions for vaccination uptake: A systematic review and meta-analysis - Malik, Amyn A.; Ahmed, Noureen; Shafiq, Mehr; Elharake, Jad A.; James, Erin; Nyhan, Kate; Paintsil, Elliott; Melchinger, Hannah Camille; Team, Yale Behavioral Interventions; Malik, Fauzia A.; Omer, Saad B. (Health policy (Amsterdam), 2023)
•Behavioral interventions improve vaccine uptake in high-income and low-middle-income countries.•The highest effect size was associated with Provider Recommendation and Onsite-vaccination.•Behavioral interventions should be employed to increase vaccination rates globally. Human behavior and more specifically behavioral insight-based approaches to vaccine uptake have often been overlooked. While there have been a few narrative reviews indexed in Medline on behavioral interventions to increase vaccine uptake, to our knowledge, none have been systematic reviews and meta-analyses covering not just high but also low-and-middle income countries. We included 613 studies from the Medline database in our systematic review and meta-analysis categorizing different behavioral interventions in 9 domains: education campaigns, on-site vaccination, incentives, free vaccination, institutional recommendation, provider recommendation, reminder and recall, message framing, and vaccine champion. Additionally, considering that there is variability in the acceptance of vaccines among different populations, we assessed studies from both high-income countries (HICs) and low- to middle-income countries (LMICs), separately. Our results showed that behavioral interventions can considerably improve vaccine uptake in most settings. All domains that we examined improved vaccine uptake with the highest effect size associated with provider recommendation (OR: 3.4 (95%CI: 2.5–4.6); Domain: motivation) and on-site vaccination (OR: 2.9 (95%CI: 2.3–3.7); Domain: practical issues). While the number of studies conducted in LMICs was smaller, the quality of studies was similar with those conducted in HICs. Nevertheless, there were variations in the observed effect sizes. Our findings indicate that “provider recommendation” and “on-site vaccination” along with other behavioral interventions can be employed to increase vaccination rates globally.